2016
DOI: 10.3168/jds.2015-10839
|View full text |Cite
|
Sign up to set email alerts
|

A single prolonged milking interval of 24 h compromises the well-being and health of dairy Holstein cows

Abstract: Cows are often shown at dairy shows with overfilled udders to achieve a better show placing. However, it is unclear to what degree "over-bagging" affects the health and well-being of show cows. The goal of this study was to assess the effect of a single prolonged milking interval (PMI) of 24h on the measurable signs of health and well-being in dairy cows in early and mid-lactation and to assess the effect of a nonsteroidal anti-inflammatory drug (NSAID) on well-being during a PMI. Fifteen Holstein cows were st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 38 publications
1
8
0
1
Order By: Relevance
“…Rumination is often assumed to be associated with good animal health (66) and well-being, especially when the cows are ruminating while lying (4); by implication, ruminating in an upright position is assumed to be associated with poor cow comfort and well-being. Further, an increased time of ruminating upright was recently reported in cows with an impaired well-being due to a prolonged milking interval, which was interpreted as a potential replacement activity for a reduced eating time (67). The fact that the lame cows in the current study spent more time Rumi up instead of Rumi down might be another measure of the impact of lameness on the well-being of tied dairy cows.…”
Section: Jaw Activities In Either Upright or Lying Posturesupporting
confidence: 52%
“…Rumination is often assumed to be associated with good animal health (66) and well-being, especially when the cows are ruminating while lying (4); by implication, ruminating in an upright position is assumed to be associated with poor cow comfort and well-being. Further, an increased time of ruminating upright was recently reported in cows with an impaired well-being due to a prolonged milking interval, which was interpreted as a potential replacement activity for a reduced eating time (67). The fact that the lame cows in the current study spent more time Rumi up instead of Rumi down might be another measure of the impact of lameness on the well-being of tied dairy cows.…”
Section: Jaw Activities In Either Upright or Lying Posturesupporting
confidence: 52%
“…A study by Bertulat et al ( 30 ) showed higher udder pressure after sudden dry-off as well as elevated levels of fecal glucocorticoid metabolites, interpreted as an indirect indicator of stress related to pain. Similarly, Kohler et al ( 31 ) investigated the potential effects of a prolonged milking interval (24 h) and found increased udder pressure, decreased eating time as well as changes in locomotion such as an increased abduction of the hind legs, possibly to avoid pressure on the udder. In the present study, the risk factors for milk leakage were early lactation (< 100 DIM) and distance transported (>100 km).…”
Section: Discussionmentioning
confidence: 99%
“…Because correlation with milking interval was high, udder edema seems to represent a pathological sign. Kohler et al (2016) demonstrated the negative effect on a cow's health and behavior after a prolonged (24-h) milking interval. Therefore, overbagging represents a remarkable welfare issue.…”
Section: Short Communicationmentioning
confidence: 99%
“…This practice is common and aims to increase the size of the udder to show the judge the milking potential of a cow. This represents an animal welfare issue because the cows' well-being is disturbed after prolonged milking intervals (PMI; Kohler et al, 2016); changes in behavior and nonphysiological status were identified in cows after PMI. Nonphysiological processes included milk leaking and edema formation.…”
Section: Short Communicationmentioning
confidence: 99%